2022
DOI: 10.1002/adma.202208272
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Versatile GeTe Thermoelectrics from Materials to Devices

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.202208272. = − + ZT S S T (3) in the above equations, T cold and T hot are cold-and hot-end temperatures. ΔT = T hot − T cold , T = (T hot + T cold )/2. S i is the Seebeck coefficient, σ i is the electrical conductivity, and κ i is the thermal conductivity with the subscript i representing n-or p-type materials. Since such a Z T is defined by assuming the temperature-independent S i , σ i , and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 275 publications
0
37
0
Order By: Relevance
“…[1] The science such as machine learning are employed to guide the finding of new thermoelectric material systems with potentially high ZTs, as well as the improvement of current thermoelectric materials. [10,11] Till now, many bulk thermoelectric materials have exhibited high experimental ZTs of >2 or even ≈3, which are promising for practical applications, such as GeTe, [12] SnSe, [9] Cu 2 Se/Te, [13] and PbTe. [14] However, these materials are difficult to keep their high thermoelectric performance when acting as thin films.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The science such as machine learning are employed to guide the finding of new thermoelectric material systems with potentially high ZTs, as well as the improvement of current thermoelectric materials. [10,11] Till now, many bulk thermoelectric materials have exhibited high experimental ZTs of >2 or even ≈3, which are promising for practical applications, such as GeTe, [12] SnSe, [9] Cu 2 Se/Te, [13] and PbTe. [14] However, these materials are difficult to keep their high thermoelectric performance when acting as thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some new material systems, including Ag 2 Se, Cu 2 Se, Mg 3 Sb 2 et al showed outstanding properties and thus performance [ 7 , 8 , 9 , 10 ]. For example, Ding et al reported an n-type Ag 2 Se film on flexible nylon membrane with an ultrahigh power factor ~9.9 μWm −1 K −2 at 300 K with excellent flexibility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, GeTe-based materials have attracted extensive attention for their promising TE applications. It is well known that the pristine GeTe is a typical p-type degenerate semiconductor with a huge number of intrinsic Ge vacancies, leading to the abundant hole carrier concentration (∼10 21 cm –3 at 300 K) . The excess carrier concentration is detrimental to the TE performance and, thus, provides a lot of room for performance optimization .…”
Section: Introductionmentioning
confidence: 99%